Faecal Transplant Therapy: A Promising Treatment Modality for Cardiovascular Diseases - Pushkala, K; Gupta, Purshottam D (Journal of Cardiology and Cardiovascular Medicine, 2023)
Cardiovascular diseases (CVD) are considered as “lifestyle” diseases and so far “No unified procedure” or medicines are effective in the management of this group of diseases. Researchers and clinicians have indicated that no safe therapeutic window is available in therapeutics at present. Recent research showed that gut microbiota are effective in managing lifestyle diseases therefore we introduced the influence of gut microbiota in the prognosis of the CVDs. Faecal transplant therapy(FMT) has been anticipated to treat many diseases similar to recurrent bacterial Clostridioides difficile infection which has been used worldwide. Recently, FMT was tried on an animal model to treat CVDs, and recent human trials that were tried to manage CVDs in humans by FMT showed encouraging results. The mechanism of action of transplanted bacteria to manage CVDs in the human population is also discussed. In-depth knowledge on the pros and cons of FMT will pave the way to standardize the procedure once the lacuna existing at present in treating CVDs, is paved, this technology will be useful for the masses.